The Role of Intravenous Immunoglobulin in Myasthenic Crisis: A Case Report of Successful Management in an Elderly Patient with Thymoma - Hanafia, Mochamad Fauzi; Adiyanto, Bowo (Faculty of Medicine, Brawijaya University, 2025)
Background: Myasthenic crisis represents the most severe and life-threatening manifestation of myasthenia gravis, affecting approximately 15-20% of patients, with mortality rates ranging from 2-16% globally. Intravenous immunoglobulin (IVIG) is emerging as a primary therapeutic modality alongside plasmapheresis for crisis management. The optimal treatment approach in elderly patients with concurrent thymoma remains challenging due to increased perioperative risks and complex clinical presentations. The present case report describes the successful management of myasthenic crisis in an elderly patient with thymoma using intensive IVIG therapy in conjunction with timely surgical interventionCase: A 71-year-old male with established myasthenia gravis presented with myasthenic crisis two days prior to scheduled thymectomy. Clinical manifestations included respiratory distress, bilateral ptosis, drooping head, and dysphonia requiring immediate intensive care management. The patient received three cycles of IVIG therapy (0.4 g/kg/day for 5 days each cycle) in the intensive care unit in conjunction with mechanical ventilation, corticosteroids, pyridostigmine, and urgent thymectomy. Treatment resulted in successful weaning from mechanical ventilation after 8 days, with complete clinical recovery and transfer to the general ward without complications.Conclusion: This case demonstrates the efficacy and safety of intensive IVIG therapy in managing myasthenic crisis in elderly patients with thymoma. The systematic administration of multiple IVIG cycles proved effective in stabilizing respiratory function and facilitating successful surgical intervention, supporting IVIG as a cornerstone therapy in critical care management of severe myasthenia gravis.